USING INSTAGRAM AS A MEDIUM IN WRITING ACTIVITY: DID IT IMPROVE STUDENTS’ WRITING QUALITY? (RETAIN, 2020)
Within the fields of education, the emergence of technology and social media has brought innovation and one of these is language. In real life, students rely not only on academic and social-life digital devices such as computers, ipads, and smartphones, but also on social media. It is presumed that the implementation of social networking sites (SNS) such as the Instagram app into the classroom would have several beneficial impacts on students, especially in the English writing class. Most students claim that writing, because of its complexity, is the most challenging skill to master. Therefore, this study aims to find out Instagram's impact on the eighth grade students in their writing efficiency. This analysis had been planned by quantitative research. Applying non-randomized sampling, this study involved two groups that were; the category of experiments and controls. There were 37 experimental group students in participation, meanwhile 27 control group students were involved. During the treament, the researcher used Instagram as a medium in writing tasks, while the control group was being taught conventionally. The research instruments were paper-based test and writing rubric assessment. The data was derived from the analyses of pre-test and post-test. Therefore the researcher used T-test calculation to calculate the results. As a result, the post-test based on paper revealed that the experimental group had a mean score of 76; while the control group was 76.74 higher. On the other hand, post-test significance level (p-value) was below 0.05, resulted in 0.000. In short, it can be presumed that Instagram can affect the writing quality of the students. Keywords: Instagram, writing skills, writing quality.